Additive manufacturing of metal-polymer hybrid parts: the influence of as-printed LPBF surface roughness on the joint strength - Belei, C.; Effertz, P. S.; Meier, B.; Amancio-Filho, S. T. (Frontiers in Materials, 2023)
As-printed Laser-Powder Bed Fusion (LPBF) surfaces can provide anchoring spots for the infiltration of polymer printed by Fused Filament Fabrication (FFF), enhancing metal-polymer joint strength. This work evaluates the influence of the as-printed LPBF surface roughness and FFF parameters on the strength of Ti-6Al-4V/PA-CF joints produced by this process combination. A three-point bending testing method based on ISO 14679:1997 was deployed, whereby the energy dissipated by the joint interface was measured. Roughness was varied by 3D-printing the substrate with different leaning angles; Height and printing speed of the coating layer (the polymer layer in direct contact with the metal) were also varied. Data was interpreted using a combination between Decision Tree and Gradient Boosting Regression, ultimately suggesting that printing speed is the prominent parameter followed by leaning angle for joint strength. Additionally, the combined effect of low printing speed and leaning angle resulted in the highest energy absorption at the interface (> 200 J).